DETERMINANTS OF COST OF FINANCIAL INTERMEDIATION IN NIGERIA’S PRE-CONSOLIDATED BANKING SECTOR - Haruna, Muhammad Auwalu (European Scientific Journal, ESJ, 2013)
In this study we investigated the determinants of cost of financial intermediation (CFI) in some selected quoted banks in Nigeria. The study used thirteen (13) banks which were drawn from the quoted banks in Nigeria. In identifying the determinants of the CFI, we estimated the two popular panel data (fixed and random effects) regression models for six (6) different measures of interest rate spread. In all, our results based on Hausman test selection and some statistical criterion shows that IMED, LLP and OE were the three most common factors that determine the commercial bank interest rate spread in all six models of measuring interest rate spread. This study therefore recommends that financial intermediation (IMED), operating expenses (OE) and Loan loss provision (LLP) be given top priority in understanding the variations in commercial banks’ cost of financial intermediation weather measured using narrow or broad interest rate spread definitions.